2021
DOI: 10.3390/life11090897
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Citral on Aquaporin 5 and Trpv4 Expressions and Uterine Contraction in Rat—An Alternative Mechanism

Abstract: Aquaporins (AQPs) are expressed in the uterus, playing a physiological role during pregnancy. An osmotic pathway—through AQP5—may modify the transient potential vanilloid 4 (TRPV4) function and uterine contraction. Our aim was to determine the role of TRPV4 antagonist citral in the regulation of pregnant uterine contraction. In vitro uterine contractions were evoked by KCl and the response was modified with citral. The expressions of TRPV4 and AQP5 were measured by RT-PCR and Western blot techniques. The lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Seres-Bokor et al [ 38 ] suggested an alternative mechanism for the relaxing effect of citral on rat uterus. A 14 day treatment in vivo with this monoterpenoid induced an increase of aquaporin channel (AQP5) expression in uterine smooth muscle, reducing hypertonic stress activation on the transient receptor potential cation channel receptor type 4 (TRPV4).…”
Section: Discussionmentioning
confidence: 99%
“…Seres-Bokor et al [ 38 ] suggested an alternative mechanism for the relaxing effect of citral on rat uterus. A 14 day treatment in vivo with this monoterpenoid induced an increase of aquaporin channel (AQP5) expression in uterine smooth muscle, reducing hypertonic stress activation on the transient receptor potential cation channel receptor type 4 (TRPV4).…”
Section: Discussionmentioning
confidence: 99%
“…Citral ((2E)-3,7-dimethylocta-2,6-dienal) is a bioactive component of lemongrass, a naturally occurring TRPV4 antagonist used to investigate the relationship between TRPV4 and AQP5 channels in the late-pregnant rat uterus [ 47 ]. It was found that AQP5 expression significantly increased, and TRPV4 expression did not change significantly after citral incubation in the 22-day pregnant rat uteri, in vitro.…”
Section: Cooperation Of Aqp5-trpv4 Channelsmentioning
confidence: 99%
“…The activation of TRPV4 leads to the Ca 2+ current, which in turn plays a role in myometrial contractions and thus in the induction of labor. The decrease in AQP5 expression on the day of delivery can be explained as a result of cell volume regulation [ 47 ].…”
Section: Cooperation Of Aqp5-trpv4 Channelsmentioning
confidence: 99%
See 1 more Smart Citation